In-vitro anti-inflammatory activity of leaves of Cicer arietinum - Supriya Mhamane (Indian Journal of Pharmacy & Drug Studies, 2024)
Cicer arietinum also known as Bengal gram. This plant belongs to the family Fabaceae. It is cultivated in India in Madhya Pradesh, Uttar Pradesh, Rajasthan, and Maharashtra. This study shows that Cicer arietinum leaves anti-inflammatory activity. It is used to decrease inflammation. This work estimates the anti-inflammatory activity of leaves of Cicer arietinum by using a UV-Visible spectrophotometer at 660nm. The maximum peak of inhibition of protein denaturation by using ethanolic and hydro-alcoholic extract is observed at 500μg/ml. By comparing both the extract ethanolic extract shows maximum percentage inhibition.